Gibberella zeae (Schw.) Petch.- A new record of ascomycetous fungus for Bangladesh (Bangladesh Journal of Plant Taxonomy, 2008)
Not available.Keywords: Gibberella zeae, Ascomycetes, BangladeshÂ DOI: 10.3329/bjpt.v15i2.1755Â Bangladesh J. Plant Taxon. 15(2): 163-165, 2008 (December)